Imaging and sentinel lymph node biopsy in high risk head and neck cutaneous squamous cell carcinoma: a Chinese cohort study - Ma, Yuedi; Shan, Dongqiu; Zhang, Haisan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the most effective modalities for detecting lymph node metastasis and to ascertain whether these procedures influenced management decisions and correlated with disease-related outcomes in head and neck cutaneous squamous cell carcinoma (HNcSCC) based on a Chinese cohort.MethodsHigh-risk HNcSCC patients were retrospectively enrolled and categorized into three groups based on neck evaluation methods: ultrasound (U), ultrasound plus CT (UC), and ultrasound plus CT plus sentinel lymph node biopsy (UCS). The impact of these modalities on regional control and overall survival was analyzed using a Cox proportional hazards model.ResultsThe U, UC, and UCS groups comprised 91, 102, and 77 patients, respectively. In the multivariable analysis for regional control, patients in the UC group exhibited a hazard ratio of 1.48 [95%CI: 1.06-2.77] compared to the UCS group, while those in the U group demonstrated an HR of 1.43 [95%CI: 1.10-3.00]. Regarding overall survival, the multivariable analysis revealed that patients in the UC group had an HR of 1.67 [95%CI: 1.11-2.89] compared to the UCS group, with the U group also presenting an HR of 1.69 [95%CI: 1.21-3.12]. The UC group exhibited a management change rate of 6.8% attributable to the addition of CT, while sentinel lymph node biopsy led to a management change rate of 7.8% in the UCS group. Among the three modalities, SLNB demonstrated the highest diagnostic accuracy, with a sensitivity of 85.7% and a specificity of 100%.ConclusionThe combination of ultrasound, CT, and SLNB resulted in improved prognostic outcomes for patients with high-risk HNcSCC.